Microwave‐Assisted Hydrothermal Synthesis of Fe2O3‐Sensitized SrTiO3 and its Luminescent Photocatalytic deNOx Activity with CaAl2O4:(Eu, Nd) Assistance. Issue 4 (28th February 2013) - Li, Huihui; Yin, Shu; Wang, Yuhua; Sato, Tsugio; Rohrer, G.
<x xml:space="preserve">Abstract</x> This work focused on the synthesis of high‐activity strontium titanate (SrTiO3) photocatalysts through an environmentally friendly process. A high energy‐efficient microwave‐assisted hydrothermal method was employed to prepare Fe‐loaded SrTiO3 that consisted of small particles around 50 nm in diameter. To achieve the effective assistance of long‐lasting fluorescence, the obtained Fe‐loaded SrTiO3 samples were coupled with CaAl2O4:(Eu, Nd). The photocatalytic activities were evaluated by the photo‐decomposition of NO. Fe loaded SrTiO3 showed high photocatalytic activities not only under visible light irradiation but also in the dark with fluorescence assistance.